Report to the trustees for the creditors of the city of Edinburgh, on the views and statements contained in an appendix [...], regarding the harbour and docks of Leith (Neill, 1835)
In: Report to the Royal Burgh Commissioners by the eight southern districts of Edinburgh, ...